Safety of Complete and Sustained Prophylaxis Withdrawal in Patients Liver-transplanted for Hepatitis B Virus-related Cirrhosis at Low Risk of Hepatitis B Virus Recurrence - Lenci, I (2011)
BACKGROUND: HBV (hepatitis B virus) reactivation after liver transplantation may be related to persistence of covalently closed circular (ccc) DNA. We investigated the safety of HBV prophylaxis withdrawal in selected HBV transplanted patients. METHODS: Thirty patients transplanted 64-195 months earlier (23 males, median age 56 years), HBsAg-positive, HBeAg, and HBV-DNA-negative at transplant (43% HCV/HDV coinfected), with undetectable intrahepatic total and ccc-DNA were enrolled. All patients underwent HBIg withdrawal and continued lamivudine with monthly HBsAg and HBV-DNA monitoring and sequential liver biopsies. Those with confirmed intrahepatic total and ccc-DNA undetect-ability 24 weeks after stopping HBIg also underwent lamivudine withdrawal and were followed up without prophylaxis. RESULTS: Twenty-five patients did not exhibit signs of HBV recurrence after prophylaxis withdrawal (median follow-up 28.7 months, range 22-42). Five patients became HBsAg-positive: one early after HBIg withdrawal, the other four after HBIg and lamivudine withdrawal. None of these patients experienced clinically relevant events. In the first patient, HBIg were reinstituted with prompt HBsAg negativization. Of the other four, one remained HBsAg-positive with detectable HBV-DNA and mild alanine transaminase elevation and was successfully treated with tenofovir. In the remaining three, HBsAg positivity was transient and followed by anti-HBs se-roconversion; thus no antiviral treatment was needed. CONCLUSION: Patients with undetectable HBV viremia at transplant and no evidence of intrahepatic total and ccc-DNA may safely undergo cautious weaning of prophylaxis, showing the low rate of HBV recurrence after a 2-year follow-up. Undetectability of intrahepatic ccc-DNA may help to identify patients at low risk of recurrence; yet studies with longer follow-up are needed.